Sistem Penunjang Keputusan Penerimaan Karyawan Menggunakan Metode Profile Matching dan Analytical Hierachy Process Pada PT. Sunny Collection - Ishak, Riswandi (www.bsi.ac.id, 2017)
Some of the problems that occur in the process of recruitment of employees in decision-making which is felt from some candidates, particularly if there are employees who have the ability and some of the other considerations that are not much different, likes and dislikes. Some of the factors that led to the company doing the hiring of employees i.e. Turnovers. These things need to be made to the company's attention because of the high turnover in a company can interfere with activities and productivity. The methods used in this research Analytical Hierarchy Process Method and Profile Matching Method that is often called the Gap. The purpose of the research is to develop a decision support system (DSS) selection to help gain employee acceptance of the results of the selection of employee acceptance for the ability of reason, intelligence, systematic thinking. The potential ability of a person is shown with the skills to solve problems, work on a heavy workload, overcoming stress due to work, making priorities or schedules, the ability of controlling emotions.